The causes and consequences of cancellations in planned orthopaedic surgery: The reactions of patients and their families - (:unkn) unknown (Churchill Livingstone, 2004)
Planned surgical interventions may be postponed for several reasons. This paper examines the causes for cancellations of the planned surgical interventions of orthopaedic patients and the reactions of these patients and their families. This descriptive study was conducted on 50 patients who were hospitalized at the Orthopaedics and Traumatology Clinic of Istanbul University Faculty of Medicine during 2002, and who were planned to undergo surgical operations. The purpose was to define the reactions of these patients and their families to the cancellation, on the day of the operation. Data were gathered using a tool developed by the researchers. Observation and face-to-face interviewing methods were used. Results showed that 34% of the patients were hospitalized for planned primary total hip replacement operations, 28% of surgical operations were cancelled because of medical conditions, cancellation decisions were made by anaesthetists with a rate of 42%. After being informed of the cancellation, 30% of patients expressed extreme negative feelings for example, "I felt as if my house collapsed down on me" and 34% of the patients expressed negative feelings such as "now my anxiety will rise and I will feel more at unease", and 54% shed tears. Thirty percent of the family members entered into a state of helpless waiting, and a further 30% of them chose to conceal their sadness from their relatives. As a result, we suggest that patient preparation for surgery be organized so as to minimize cancellation possibilities and, when a cancellation is inevitable, to describe the event with its reasons thoroughly to the patient and his/her family. © 2003 Elsevier Ltd. All rights reserved.
Keywords: Cancellation; Orthopaedic surgical operations; Patient and family reactions